PEMBERDAYAAN PETANI: STRATEGI PENINGKATAN pCil1l1llgl<.ahul kesejahtcraan petani. KESEJAHTERAAN DI PEDESAAN - Hastuti, Hastuti (Jurnal Cakrawala Pendidikan, 2016)
The fanners who so far have been liing in a dcspreate condition undergone worse condition because they have to face the impact of economic crisis has be gun since the decrease of rupiah exchange towards the USA , because the price of terti Iizer is so high that the farmers can not buy it. The governlnent policy by increasing the basic prices of agricultural production, especially the basic price of rice ’Hake farm r’s condition is more difficult because they do not have bargaining position. Part of Indonesian farmers are the lower who have a narrow land, lower incolne, and less education that anakc thenl live in poverty. I n order to increase their welfare, the farmers should try to find alternative sources at income by clnpowcnnent so that they will be able to use and to Jcvelop this agricultural sectors. Empowennent the I arnlers so select the cOlll0dity of agricultural production wich is oriented to market need, such as with developing the agrindustry. In fact, the agricultural sector in the nationally economic decrease has resistence for supporting the farmer’s life, although it is not Inuch pospective. The difficulty that appears is that the caracteristic of Indonesian farmers who have not been ready yet to face the competitive ularket. Enlpowernlcnt of farnlers in rural areas can be dOlll’ by optinlalizing the role of social institution, incrcasing the education level and mastering science and or programs. The government onl serves as a facilitator and guide. wich has mediator function motivator and also f tcilitator and dinanlisator , so that the farmers are encouraged to be more empowerment and to b